PENGGUNAAN ZPA HASIL EKSTRAK KULIT POHON RAMBUTAN RAPI’AH UNTUK PEWARNAAN BATIK CELUP MENGGUNAKAN TEKNIK FIKSASI - MR Santosa, kaffah imanuddin; Listiani, Sri (Practice of Fashion and Textile Education Journal, 2023)
In its development, batik has become a trend that is not only a formal dress. In the contemporary era, batik is widely used as a variety of everyday clothing models. Batik is also a cultural heritage that contains meaning from each of its visuals. In Indonesia, batik is known to have a variety of motifs originating from several different regions. Batik is a technique also known as dyeing natural fiber fabrics using a resistance dyeing technique. The parts of the cloth become patterned because when they are dipped in the liquid color, there are parts that are deliberately obstructed. It is the part of the cloth that is blocked that gives rise to the pattern of the batik motif. (Tocharman, 2009) Batik dyes generally use chemicals that can have a negative impact on the environment. However, due to its practical nature and production quantity orientation, it has become a conventional coloring medium. Indonesia is a country rich in natural resources. This condition requires us to be able to exploit and explore natural resources properly. One of the natural resources that can be used in the batik industry is natural dyes (ZPA). The process of using natural colors in batik techniques has been carried out by our ancestors for generations until synthetic colors were found which were considered practical and economical. The rambutan tree is a tree that can be found in Indonesia. Apart from the fruit, the authors assume that there is a lot of sap contained in the rambutan rapi'ah tree trunk, so that the rambutan tree bark can be used as a natural dye in batik. This study used descriptive qualitative methods with experiments on mori cloth which is commonly used as batik cloth to see the results of the colors produced from the rambutan tree extract using various fixations.